Economic affordability of food as a component of the economic security of Ukraine - Yurii, E.A.; Mostenska, T.L.; Mostenska, T.G.; Lakner, Z.; Vasa, L. (PLoS ONEthis link is disabled, 2022)
Economic security can be considered as an economic aspect of the life of an individual or household that provides the opportunity to achieve financial stability and improve living standards. In this context, understanding the impact of economic affordability of food on the economic security of the country is of great importance. The authors propose to use the indicator of economic affordability of food for in-depth analysis of the economic security of the country. Indicators that determine the level of economic affordability of food products in Ukraine for 2000–2018 are calculated. The regression analysis made it possible to establish a close relationship between the indicators of food expenditures and the level of GDP per capita, between the level of income and expenditure of food of decile groups. Correlation coefficients between the consumption of six basic foodstuffs and the level of per capita income in Ukraine are determined. The obtained indicators, which determine the economic affordability of food, allow us to conclude that there is a lack of economic protection at the level of individual low-income households. Overcoming economic instability and minimizing the possible consequences of the low level of economic affordability of food should become one of the main tasks of Ukraine’s economic security.